Inovasi Manajemen Kurikulum Sanggar Kutubut Turots - Abdul Wahab; Gatot Sujono; Afif Zamroni (Chalim Journal of Teaching and Learning (CJoTL), 2021)
This article aims to describe and analyze curriculum planning; (2) curriculum organization; (3) curriculum implementation; and (4) curriculum evaluation at SMP Bilingual Terpadu 2 Junwangi Sidoarjo. This article uses a type of qualitative research with a case study approach. The results of this study are: (1) The curriculum planning of Kutubut Turost Studio in Bilingual Terpadu 2 Junior High School is based on the vision, mission, and goals of the school. (2) The organization of the Kutubut Turost Studio curriculum at the Bilingual Terpadu 2 Junior High School is divided into four areas that handle tasks proportionally with the aim of facilitating the implementation of the curriculum. The four fields include the Santrian Division which consists of the student council and the SKT and STE program, the Curriculum Division (7 student obligations) dealing with prayer discipline, language discipline, learning discipline, hygiene discipline, and security discipline, extra-curricular fields including tausiyah and ACEN recitations, PGPQ and reading the Qur'an, Muhadharah, Haulya qoryah, PJ Guest House and other extras and the field of pesantren economics including cooperatives, canteens & restaurants, ALBER and Wartel. (3) Implementation of the curriculum, namely the class level through the division of teaching tasks and the boarding school level through learning activities in the classroom and activities outside the classroom. (4) The evaluation of the curriculum carried out at the Kutubut Turost Studio at the Bilingual Terpadu 2 Junior High School was based on several things, namely: based on needs and suitability, and based on proposals based on semester exam results and observations made by homeroom teachers and tutors. Meanwhile, there are three curriculum evaluations conducted by Sanggar Kutubut Turost at SMP Bilingual Terpadu 2, evaluation in the cognitive field, evaluation in the field of character and personality, and the last evaluation in the field of discipline.